The Impact of Social Media Influence and Online Shopping Habits on Consumer Behavior and Social Identity in the Digital Economy in Indonesia - Frans Sudirjo; Soesanto, Dasa Rahardjo; Susilo, Anton (The Eastasouth Journal of Social Science and Humanities, 2024)
This study examines the impact of social media influence and online shopping habits on consumer behavior and social identity in the context of Indonesia’s digital economy. Using a quantitative approach, data were collected from 280 respondents through a Likert-scale questionnaire, and Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed to analyze the relationships. The results reveal that both social media influence and online shopping habits significantly affect consumer behavior and social identity. Additionally, consumer behavior and social identity were found to contribute strongly to the growth of the digital economy. The findings highlight the pivotal role of digital platforms in shaping consumer actions and identities, driving Indonesia’s digital economy. The study provides practical insights for businesses to leverage social media and e-commerce in influencing consumer behavior and for policymakers to foster a supportive digital infrastructure.